Frequency of self-monitoring of blood glucose in patients with type 2 diabetes: association with hypoglycaemic events. - Farmer, A; Balman, E; Gadsby, R; Moffatt, J; Cradock, S; McEwen, L; Jameson, K (2008)
OBJECTIVE: The objective of this study is to describe current self-monitoring of blood glucose (SMBG) practice for patients with type 2 diabetes by treatment type and adherence with healthcare professional advice concerning SMBG. In addition, the study aims to investigate the association of SMBG and self-reported episodes of low blood glucose. DESIGN AND SETTING: This cross-sectional survey design study was carried out on patients with type 2 diabetes aged 18 years or over, attending community pharmacies in 97 sites across the United Kingdom. METHODS: Patients picking up a prescription for blood glucose test strips or diabetes medicine from a community pharmacist were asked to complete a questionnaire. The pharmacist was available to assist if requested. Questions included: self-reports of frequency of blood glucose testing; type of diabetes treatment; advice given by healthcare professionals about frequency of blood glucose testing; frequency of episodes of low blood glucose; and last known HbA(1c) level. The final sample size was 554 respondents, who were grouped for analysis as follows: those being treated with insulin, either alone or with any oral medication (n = 167); those being treated with sulfonylureas, either alone or with any oral medication (n = 187); and those being treated with any other medication, or controlled by diet and exercise alone (n = 202). RESULTS: Frequency of SMBG was higher in patients using insulin (median 10 times per week, Q (1), Q (3) = 4.5, 14) than in patients on treatments other than insulin (four times per week, Q (1), Q (3) = 2, 7, p < 0.001). SMBG was carried out at the same frequency in patients not treated with insulin regardless of whether they were prescribed sulfonylureas. Greater frequency of SMBG was associated with self-reports of one or more episodes of low blood glucose in the previous six months. CONCLUSIONS: Among patients with type 2 diabetes, those treated with insulin used SMBG at a greater frequency than those not treated with insulin. Increased frequency of testing was associated with increased frequency of self-reported episodes of low blood glucose, even among patients not taking insulin or sulfonylureas. This raises the possibility that episodes of hypoglycaemia may not be accurately identified, leading to unnecessary fear, or conversely that treatment is not being adjusted to avoid such morbidity. Although further work is needed to explore this association in a representative, prospective cohort of patients, possible explanations for reports of low-blood glucose should be discussed with patients using SMBG more frequently to ensure they are able to accurately identify episodes of hypoglycaemia.